Pengaruh Model pembelajaran Giving Question and Getting Answer Terhadap Hasil Belajar IPS Siswa Sekolah Dasar - Fitra, Ainal; Aeni Rahman, Syarifah; Yanty Muchtar, Fitri (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
AbstractThe main problem in this study is that learning activities are still centered on the teacher, students are less focused on learning and often complain of boredom in learning, resulting in a decrease in learning outcomes for Social Science skills. This study aims to determine the effect of the Giving Question and Getting Answer learning model on the learning outcomes of Social Science of grade V students of SDN 48 Lappae, Sinjai Regency. The type of research used in this study is Pre-Experimental Design and is a type of quantitative research. The sample in this study was 22 students. Data collection techniques were carried out using learning outcome tests and observation sheets. Data analysis techniques in this study were descriptive data analysis techniques and T-Tests. The results of the study showed that the learning outcomes of Social Sciences before the application of the Giving Question and Getting Answer learning model in the pretest had an average value of 60. While in the posttest there was an increase with an average value of 80. The results of the t-test analysis regarding the effect of the Giving Question and Getting Answer learning model on student learning outcomes showed that the significance value obtained was good, namely the effect of the Giving Question and Getting Answer learning model on Social Sciences learning outcomes (Sig = 0.611) was smaller than the specified alpha value of 0.05 (0.550 0.05). Based on the results obtained, it can be concluded that Ho is rejected and H1 is accepted, which states that there is an effect of using the Giving Question and Getting Answer learning model on the learning outcomes of Social Sciences of class V students of SDN 48 Lappae, Sinjai Regency.KeywordsGiving Questions, Getting Answers, Learning Models, Students, ThematicLearning Outcomes